New Urban Immigrants : The Korean Community in New York - Kim, Illsoo, 1944- (Book collections on Project MUSE., 1981)
Insofar as the new immigration is both structurally and functionally distinct from the old immigration of peasants and artisans, the author dispenses with the traditional paradigm of a folk-to-urban transition and focuses instead on such macroscopic features as the internal political and economic problems, social structure, and foreign policy of the homeland; on the international trade, economic structure, and immigration policy of the host country; and on the special qualities of immigrants who are urban, educated, and middle class. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.